OPTIMASI CAIRAN PEMBANGKIT MESIN PENCUCI FILM RADIOGRAF PADA LABORATORIUM FISIKA MEDIK UNNES - Rahayu Ningtias, Diah; Susilo, S.; Sutikno, S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2013)
Automatic film washing machine (TAEHN, model TM 300E in Physics Laboratory of FMIPA Unnes was successfully optimized by variating temperatures of developer and fixer solution in the range of 28˚C until 40˚C with temperature interval of 2˚C. At the first, developer solution was variated at controlled fixer temperature namely 30˚C, then it was analyzed to fixer determine density of each radiograph film. The optimum temperature of developer solution is available to varying temperature of fixer solution. The optimum temperatures of developer solution and fixer solution are 32˚C and 32˚C, respectively.